Socializing Financial Report Preparation for MSMEs Based on Financial Accounting Standards (SAK EMKM) - Muhammad,; Purnamasari, Fitri; Edwy, Ferby Mutia; Anugrahani, Inanda Shinta; Kristanti, Clara Agustina; Rahayu, Ika Listiana; Dewanti, Rosa Nidya; Roziin, Ahmad Wafi Amal Abu (Jurnal Pengabdian Masyarakat, 2025)
Purpose: MSMEs are vital to Indonesia's economy, absorbing 97% of the workforce, but face challenges with limited capital and low financial literacy in preparing reports. This program aims to enhance the financial literacy of MSME actors in Malang, focusing on the preparation of financial reports based on applicable accounting standards. Method: The program included lectures to introduce the Financial Accounting Standards for Micro, Small, and Medium Entities, followed by interactive discussions and question-and-answer sessions to help MSME actors apply the standards to their businesses. Practical Application: This program aims to help MSME actors prepare standardized financial reports based on SAK EMKM, improving their chances of securing loans and investments. By enhancing financial literacy, MSMEs can manage their businesses more effectively and sustainably. Conclusion: The results of the activities show an increase in participants' knowledge regarding the basic concepts of SAK EMKM, measuring assets and liabilities, and presenting financial reports.